A study on the impacts of working from home towards employee’s engagement in Institut Sukan Negara / Farieyza Farhaniey Mohd Fauzi and Aisyah Zanariah Roslan Abdul Ghani - Mohd Fauzi, Farieyza Farhaniey; Roslan Abdul Ghani, Aisyah Zanariah (2022)
This study aims to investigate the Impact of Working from Home Towards Employee’s Engagement. This study uses quantitative data. A survey of 115 respondents, representing employees from Institut Sukan Negara. The outcomes of the analysis revealed that there is significant relationship between employee’s engagement and factors of employee’s productivity, employee’s financial constraint, employee’s working environment and employee’s stress level. Based on the finding discussed, all four independent variables used, which are employee’s productivity, employee’s financial constraint, employee’s working environment and employee’s stress level, have significant and positive relationship towards employee’s engagement while working from home and employee’s productivity is the most significant among other independent variables. This demonstrates that using these four variables can affect employee’s engagement while working from home.